2010
DOI: 10.1007/s00442-010-1677-2
|View full text |Cite
|
Sign up to set email alerts
|

Oil pollution increases plasma antioxidants but reduces coloration in a seabird

Abstract: It has been suggested that condition-dependent signals may be a useful measure of environmental quality. In this study, we tested the hypothesis that oil pollution enhances oxidative stress and impairs expression of a carotenoid-based signal in a wild population of the yellow-legged gull (Larus michahellis). During the courtship period, a group of gulls were fed a supplementary diet containing heavy fuel oil from the Prestige oil spill and were compared with control gulls fed a similar supplementary diet witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 84 publications
3
21
1
Order By: Relevance
“…Thereby, our study provides evidences that POPs contamination can affect integument carotenoidbased colouration. This is consistent with previous work since Pérez et al (2010a) showed that organic compounds negatively influence the red bill spot size of adults yellow-legged gulls (Larus michahellis) during the courtship period. Moreover, Bortolotti et al (2003) found that colouration of ceres and lores were disrupted by an enriched-PCB diet in captive American kestrels: exposed males were duller than controls, and juveniles of both sexes were brighter in winter.…”
Section: Pops and Integument Colourationsupporting
confidence: 93%
See 4 more Smart Citations
“…Thereby, our study provides evidences that POPs contamination can affect integument carotenoidbased colouration. This is consistent with previous work since Pérez et al (2010a) showed that organic compounds negatively influence the red bill spot size of adults yellow-legged gulls (Larus michahellis) during the courtship period. Moreover, Bortolotti et al (2003) found that colouration of ceres and lores were disrupted by an enriched-PCB diet in captive American kestrels: exposed males were duller than controls, and juveniles of both sexes were brighter in winter.…”
Section: Pops and Integument Colourationsupporting
confidence: 93%
“…Under this scenario, female kittiwakes with the highest POP levels could allocate preferentially their carotenoids towards protective physiological functions (immunity, antioxidant capacity) whereas female kittiwakes with the lowest POP levels could allocate preferentially the available carotenoids towards sexual signaling. These results are thus consistent with the existence of a trade-off between allocations of carotenoids to sexual ornaments signaling versus physiological functions for detoxification processes (Pérez et al, 2010a). However, we did not perform any physiological analysis in our study and, thus, the existence of this trade-off could only be confirmed by coupling integument and plasma carotenoid measurements and POP levels in future studies.…”
Section: Pops and Integument Colourationsupporting
confidence: 87%
See 3 more Smart Citations